Effects of different lipids on the physicochemical properties and microstructure of pale, soft and exudative (PSE)-like chicken meat gel. (June 2021) - Lan, Meijuan; Li, Lin; Peng, Xiaolong; Chen, Juncheng; Cao, Qiuhua; He, Ni; Cai, Jiaxian; Li, Bing; Zhang, Xia
Abstract: The objective of this study was to determine effects of lipids on the physicochemical properties and microstructure of pale, soft and exudative (PSE)-like chicken gel. The PSE-like chicken meat gels prepared with lipid possessed higher lightness, whiteness, water-holding capacity but lower hardness, gumminess and chewiness, compared to the gels prepared without lipid. The secondary structure analysis showed that PSE-like meat gels presented increased β-sheet content after adding sunflower oil and peanut oil. Furthermore, the magnetic resonance imaging (MRI) results suggested that lard significantly increased the water holding capacity of PSE-like meat gels (P < 0.05), and the environmental scanning electron microscope (ESEM) results revealed an increase of matrix disorganization and some loss of spongy appearance among the meat gels with the addition of lipids. Sensory evaluation indicated that PSE-like meat gels with lipids had no difference in flavor, springiness and chewiness, but color was more intense and texture was softer compared with meat gels without lipid. Overall, these results suggested that lipid addition improves the functionality of PSE-like chicken meats and increase the economic benefits for the poultry industry. Highlights: Effects of peanut oil, sunflower oil and lard on PSE-like meat gelation were studied. The sunflower oil and peanut oil increased β-sheet contents in the PSE-like meat gels. The water holding capacity of PSE-like meat gels was improved as lard was added.